Technology Acceptance Model (TAM) on distance learning in University of Brawijaya - Mega Yuda Rukmana; Fitra Abdurrachman Bactiar; Sabriansyah Rizqika Akbar (Journal of Information Technology and Computer Science, 2024)
The shift from traditional classroom settings to online learning has become prevalent in most higher education institutions. A key tool facilitating this transition is the Learning Management System (LMS). Commonly used e-learning platforms include Google Classroom and Zoom. This research was aimed to identify the factors that influence the students’ acceptance of technology in the education field. It involved the master's students in the computer science program at Brawijaya University as the participants. To fill in the gap in the previous research, the research employed the Technology Acceptance Model (TAM), incorporating additional external factors such as the impact of application features and their interoperability. The methodology involved formulating hypotheses and using path analysis to examine the relationships between these factors. The results revealed that the variables PE, PEX, EEX, FC, PI, and PA influence both Perceived Ease of Use (PEOU) and Perceived Usefulness (PU), with values of significance below 0.05. Similarly, PEOU and PU are shown to significantly affect actual system use.